Controlled pyrolysis of ionically self-assembled metalloporphyrins on carbon as cathodic electrocatalysts of polymer electrolyte membrane fuel cells. (16th March 2021) - Zhai, Zihui; Liu, Qiunan; Zheng, Ruonan; Qiu, Chenxi; Qin, Jiaqi; Li, Jia; Xie, Yan; Wang, Anjie; Huang, Jianyu; Song, Yujiang
Abstract: Pyrolysis of metalloporphyrin can improve the performance toward oxygen reduction reaction (ORR) that largely governs the properties of hydrogen polymer electrolyte membrane fuel cells (PEMFCs). However, pyrolysis frequently causes the aggregation of metal centers of metalloporphyrins and deteriorates the retention and/or creation of ORR active sites. Control over the pyrolysis of metalloporphyrins has rarely been done. The pyrolysis of ionically self-assembled cobalt (III) and iron (III) metalloporphyrin on EC600 was studied for the preparation of ORR electrocatalysts. As evidenced by high-angle annular dark field-scanning (HAADF) transmission electron microscopy (TEM) and 57 Fe Mössbauer spectroscopy, an atomically dispersed electrocatalyst was obtained with probable porphyrin-like Fe and Co sites dispersed in the carbon matrix. We speculate that the electrostatic interaction between the porphyrins and the interaction between the porphyrins and carbon should contribute to the formation and/or retention of atomically dispersed ORR active sites. Our electrocatalyst displays decent ORR performance in alkaline solution. Graphical abstract: Image 1 Highlights: Ionically self-assembled porphyrins on carbon were heat-treated. Single-atom catalyst was obtained in the absence of nanoparticles and clusters. Electrostatic and π-π interaction may account for the formation of single-atom sites.